Bioethical aspects of alcoholism - Tempesta, Enrico; Zeppetelli, Ermelinda (Medicina e Morale, 1989)
Alcoholism represents one of the major clinical and public health problems in the world and especially in states with higher socio-economic development, where the importance and severity of the problems posed both at the level of the individual and the community. The problems are therefore enormous, yet it is only in recent years that the search for the most appropriate means of combating the phenomenon has been forced upon us. Committed more seriously to directly addressing alcoholism rather than its many consequences.